Nc-5 gene-dependent molecular identification and phylogenetic investigation of Neospora caninum in sheep - Azhar C. Al-Shabany; Mansoor J. Alkhaled (Iraqi Journal of Veterinary Sciences, 2024)
The current study was conducted to identify the occurrence of Neospora caninum in sheep using molecular techniques. The investigation included 200 sheep samples (20 heart and 80 brain tissues and 100 blood) collected from different Al-Qadisiyah Province, Iraq districts. After extracting the DNA, the samples were subjected to molecular techniques, polymerase chain reaction (PCR), and partial gene sequencing accompanied by estimating the phylogenetic status of the N. caninum coccidial microorganism. Both techniques relied on detecting the Nc-5 gene, a repetitive region of the organism's DNA. The finding of the PCR revealed the genetic identification of 7 (3.5%) isolates of N. caninum in the samples of the examined sheep. For the sequencing, seven PCR products were detected as N. caninum with nucleotide close similarity to isolates from some regions, such as New Zealand and Switzerland. The findings demonstrated by the herein study that sheep can be an intermediate host for Neospora caninum; however, all these global isolates were reported only from species other than from sheep; the current study target animals.